Outcomes of antibiotic therapy and transvaginal ultrasound-guided efficacy of transvaginal ultrasound-guided drainage in treating tubo-ovarian abscesses: Three case reports - Zahra Heidar; Tayebeh Esfidani; Atefeh Moridi; Mahtab Anvari (International Journal of Reproductive BioMedicine)
Background: To introduce minimally invasive methods for the successful treatment of tubo-ovarian abscesses (TOAs), an antibiotic regimen was considered the first line of treatment. However, in some cases, this approach fails, and another intervention (laparotomy or minimally guidance drainage) is required.